Ideology and Subtitling: South African Soap Operas - Kruger, Jan-Louis (Meta, 2012)
This article investigates the ideological component of patronage in the subtitling of four South African soap operas: Generations, 7de Laan, Muvhango, and Isidingo. Taking the concepts introduced by Lefevere as point of departure, the article first discusses the various ways in which audiovisual translation (AVT) is subject to manipulation. This manipulation is shown to be a result of the fact that subtitles, as text superimposed onto the image during post-editing, thereby obscuring a small part of the screen, constantly foregrounds itself to the audience. This foregrounding is also affected by the linguistic background of the audience – whether or not they understand the original dialogue. The argument then turns to a discussion of AVT, and specifically subtitling, as rewriting. The link between language and ideology is discussed as it pertains to issues of power, particularly related to the role of English in the media, also in South Africa, where, in Gottlieb’s terminology, South Africa can be described as a multilingual anglophile context. The language policy of the South African Broadcasting Corporation is then discussed in terms of patronage and ideology followed by a discussion of the role of ideology in these four locally-produced soap operas. In this discussion the different ways in which the subtitling practices of the soap operas reflect ideology are investigated. The article concludes that accessibility plays a smaller role in subtitling in South Africa than the ideology of multilingualism and multiculturalism.